Croatian National Data and Comparison with European Practice: Data from the Cardiac Resynchronization Therapy Survey II Multicenter Registry - Sandro Brusich; Ivan Zeljković; Nikola Pavlovic; Ante Anić; Zrinka Jurišić; David Židan; Marina Klasan; Zlatko Čubranić; Kenneth Dickstein; Cecilia Linde; Camilla Normand; Sime Manola (Cardiology Research and Practice)
Aims. The Cardiac Resynchronization Therapy (CRT) Survey II was conducted between October 2015 and December 2016 and included data from 11088 CRT implantations from 42 countries. The survey’s aim was to report on current European CRT practice. The aim of this study was to compare the Croatian national CRT practice with the European data. Methods. Five centres from Croatia recruited consecutive patients, in a 15-month period, who underwent CRT implantation, primary or an upgrade. Data were collected prospectively by using online database. Results. A total of 115 patients were included in Croatia, which is 33.2% of all CRT implants in Croatia during the study period (total n=346). Median age of the study population was 67 (61–73) years, and 21.2% were women. Primary heart failure (HF) aetiology was nonischemic in 61.1% of patients, and HF with wide QRS was the most common indication for the implantation (73.5%). 80% of patients had complete left bundle branch block, and over two-third had QRS ≥150 ms. Device-related adverse events were recorded in 4.3% of patients. When compared with European countries, Croatian patients were significantly younger (67 vs. 70 years, p=0.012), had similar rate of comorbidities with the exception of higher prevalence of hypertension. Croatian patients significantly more often received CRT-pacemaker when compared with European population (58.3 vs. 29.9%, OR 3.27, 95%CI 2.25–4.74, p<0.001). Conclusion. Our data indicate strict selection of patients among HF population and adherence to guidelines with exception of higher proportion of CRT-pacemaker implantation. This is likely to be influenced by healthcare organization and reimbursement issues in Croatia.